1988
DOI: 10.1136/bmj.296.6639.1759
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravesical mitomycin C on recurrence of newly diagnosed superficial bladder cancer: interim report from the Medical Research Council Subgroup on Superficial Bladder Cancer (Urological Cancer Working Party)

Abstract: A randomised control trial of intravesical instillation of mitomycin C was conducted in 457 patients with cancer of the bladder that was confined to the submucosa on histological examination. The events studied were the recurrence free rate, the recurrence rate/year, and the number of new tumours developing/year. At the initial cystoscopy the tumours were completely resected and the patients randomised to have no instillation of mitomycin C, a single instillation of 40 mg in 40 ml of water at that cystoscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 9 publications
3
39
0
Order By: Relevance
“…The early intravesical instillation of 40 mg of mitomycin C shortly after transurethral resection has been shown to reduce the rate of recurrence of superficial bladder carcinoma significantly. This was initially reported by Tolley et al [10] and later confirmed by other study groups as well [2,9,11]. However, several complications of intravesical mitomycin resulting in necrotic tissue damage have been reported [3,5,7].…”
Section: Introductionsupporting
confidence: 73%
“…The early intravesical instillation of 40 mg of mitomycin C shortly after transurethral resection has been shown to reduce the rate of recurrence of superficial bladder carcinoma significantly. This was initially reported by Tolley et al [10] and later confirmed by other study groups as well [2,9,11]. However, several complications of intravesical mitomycin resulting in necrotic tissue damage have been reported [3,5,7].…”
Section: Introductionsupporting
confidence: 73%
“…In two Medical Research Council (MRC) trials, which were each published twice [8][9][10][11], four additional 3 monthly instillations were given during 1 yr. In the thiotepa study [8,9], there was no reduction in the percentage of patients who had recurrence, 41.9% versus 37.5%; however, this trial has been criticized because of the low drug concentration used, 30 mg/50 ml.…”
Section: After One Immediate Instillation Can Additional Intravesicamentioning
confidence: 99%
“…In the thiotepa study [8,9], there was no reduction in the percentage of patients who had recurrence, 41.9% versus 37.5%; however, this trial has been criticized because of the low drug concentration used, 30 mg/50 ml. In the mitomycin C (MMC) trial [10,11], based on updated summary data, there was a reduction in the percentage with recurrence from 48.3% to 36.3% overall (p = 0.04) and from 70% to 50% in patients with multiple tumors (p = 0.09). However, in both of these studies, patients who recurred at 3 mo prior to starting their additional instillations were already counted as having their first recurrence, potentially diluting the size of any treatment effect.…”
Section: After One Immediate Instillation Can Additional Intravesicamentioning
confidence: 99%
“…There are controversial results from studies evaluating the adjuvant role of a single, postoperative intravesical instillation of chemotherapy regimens such as epirubicin, mitomycin C and gemcitabin within 24 hours after transurethral resection (Tolley et al, 1988;Oosterlinck et al, 1993;Hall, 1997;Brocks et al, 2005 of NMIBC recommend that all patients receive one immediate instillation of chemotherapy after TUR. In patients at low risk of recurrence and progression, no further treatment is recommended prior to a subsequent recurrence.…”
Section: Introductionmentioning
confidence: 99%